Perancangan Produk Interior Kelas Premium Dengan Pengembangan Kreativitas Upcycling Kayu Bekas Peti Kemas - William Vijadhammo Lumintan; Yusita Kusumarini; Filipus Priyo Suprobo (Intra, 2019)
Port of Tanjung Perak which located at Surabaya became the import-export trading center in East Java. Hence the cargo container can be seen pilling up in North Surabaya. This event was directly proportional to the pilling up of ex-container wood. If this happen often, then the amount of ex-container wood would be pilling up, weathered until broken, and eventually become city trash. Whereas if it’s reviewed again, ex-container wood had hidden potentials. This research aims to understand the characteristics, treatment, and processing technique of ex-container wood, then re-use the ex-container wood with creative development of its potential. Design process done using design thinking methods, which is: inspiration (empathize, understand, define), ideation (ideate, prototype, test), and implementation (storytelling, pilot, business model). The result of this design were 4 design sets of interior products which consist of stool, side table, bench, and coffee table, 3 sets of exhibition booth design, 1 set of product and booth realization, company brand and its advertising media. This project proved that ex-container wood can actually be used again using upcycling technic, with creative development of its potential, and became premium class interior product.